The immatures of Bezzia chilensis Spinelli & Ronderos, 2001 (Diptera, Ceratopogonidae) - Anjos Dos Santos, Danielle (2018)
The fourth instar larva and the pupa of Bezzia chilensis Spinelli & Ronderos, 2001 are described for the first time. The immature stages were collected from macrophytes and filamentous algae in streams of the Patagonian steppe, in the provinces of Neuquén and Chubut, Argentina. The described stages were photographed and illustrated with a phase-contrast microscope and scanning electron microscope. Data on the bionomics of the species, new records and tables for characters of the known larvae and pupae of Bezzia Kieffer, 1899 from the Neotropical region are provided.